Eksploitasi Anak Jalanan Sebagai Manusia Silver Di Kota Bandar Lampung - Zainudin Hasan; Refi Shely Ristianti; Elin Novita; Sarah Uli Ferianti (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Silver man is widespread in big cities in Indonesia, such as Jakarta, Surabaya, Yogyakarta, Bandung, and Lampung, and is expected to breed in 2020.Purposes of the Research: The purpose of this study is to describe one form of child exploitation, namely the silver man in the city of Bandar LampungMethods of the Research: The research methodology used is a normative legal research methodology.Results of the Research: Based on the results of the study, several children who became silver humans in Bandar Lampung City were reported to have done it on their own accord. Some claim that silver men have agencies that actively recruit them from various regions and place them in specific locations, usually at urban red lights. There are more silver age people who are children than those who drop out of school because these people cannot continue their education because of the weak economy. Some of them are still in school.